Concentration and moment of niacin application on Urochloa brizantha in relation to nitrogen fertilization - Silva, Higor Jonathan de Oliveira; Souza, Maria Ingrid de; Vendruscolo, Eduardo Pradi; Rochetti, Ana Carolina Alves; Rodrigues Sant’Ana, Gabriela (Revista de Ciências Agroveterinárias, 2022)
The present study aimed to evaluate the effect of applying different concentrations of niacin, at different times in relation to nitrogen fertilization, on the characteristics of Urochloa brizantha. The treatments consisted of applying three concentrations of niacin (0, 100, and 200 mg L-1) and three different moments (two days before, together, and two days after nitrogen fertilization). It was found that there was variation in response, mainly concerning the moment of application of the vitamins, in which the joint and subsequent application of fertilization generally exceeded the application performed previously, and of both concentrations used (100 and 200 mg L-1), in relation to the control without vitamin application. In this way, the application of niacin at a concentration of 100 mg L-1, carried out jointly or after nitrogen fertilization, provides better conditions for developing and producing dry matter of Urochloa brizantha due to the presence of nitrogen.